Keeping Abreast of Foreign Fashions: Rationalizing Rūs Brooches in a Sixteenth-Century Persian Version of Ibn Faḍlān’s Risāla - Upham, Tonicha Mae (Medieval encounters, 2022)
Studies of Ibn Faḍlān’s tenth-century Risāla, a travel account detailing his journey from Baghdad to the banks of the Volga River, typically rely on thirteenth-century witnesses to the original travelogue. These are our earliest and fullest versions of the text, but are not the only extant records of Ibn Faḍlān’s journey. Due to both its late dating and its spurious interpolations, the partial preservation of the Risāla in Amīn Rāzī’s sixteenth-century geographical work, Haft Iqlīm, is frequently overlooked. This article reconsiders attitudes to Amīn Rāzī’s work, focusing on his claim that Rūs women used oval brooches to restrict the growth of their breasts. Approaching this claim using classical, Arabic, and Persian analogues of breast restriction, cauterization, Amazons, and Islands of Women, and tracing geographical and literary dissemination, Amīn Rāzī’s “rationalization” of Rūs women’s costume will be reframed as the plausible conclusion of a number of robust and longstanding geographical traditions.